Sex and age‐related differences in perceived, desired and measured percentage body fat among adults. Issue 5 (30th June 2014) - Campisi, J.; Finn, K. E.; Bravo, Y.; Arnold, J.; Benjamin, M.; Sukiennik, M.; Shakya, S.; Fontaine, D.
Abstract: Background: Body image distortion/discrepancy leads to psychological stress, disordered eating and mental and physical disease. To begin to assess body image distortion/discrepancy, we compared perceived, desired and measured percentage body fat in male versus female and college‐aged versus non‐college aged individuals. In addition, we assessed the acute stress response to body composition measurement. Methods: Body fat percentage of 15 college aged ('College Students'; CS) (mean = 19 years) and 16 non‐college aged ('Non‐College Aged Students'; NCS) (mean = 39 years) males and females was assessed with the BodPod Body Composition Tracking System (Life Measurement Instruments, Concord, CA, USA). Participants indicated their perception of body fat and their desired body fat using a somatomorphic matrix. Salivary cortisol, heart rate and blood pressure were also measured. Data were analysed by analysis of variance and alpha was set at 0.05. Results: Mean (SD) percentage body fat of males [15.2% (6.1%] was significantly lower than that of females [28.4% (6.4%)] ( P < 0.0001). Both CS and NCS females perceived their body fat to be lower (5%) than measured body fat and desired their body fat to be lower (12%) than measured ( P < 0.05). CS and NCS male participants demonstrated the opposite result; both CS and NCS male populations perceived their body fat to be higher (5%) than measured body fat and desired their body fat to be higher (4%) than measured ( P < 0.05). No differences between any groups were observed in heart rate, blood pressure or cortisol response to body fat measurement. Conclusions: Sex‐related but not age‐related differences in perceived, desired and measured percentage body fat were observed.